Order estimates for the approximative characteristics of functions from the classes $S_{p,θ}^{Ω} B(R^d)$ with a given majorant of generalized mixed modules of smoothness in the uniform metric - Yanchenko, S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We establish the exact-order estimates of approximation for the classes $S_{p,θ}^{Ω} B$ of functions of several variables defined on$R^d$ in the norm of $L_{∞} (R^d)$ by entire functions of exponential type with supports of their Fourier transforms in the setsgenerated by the level surfaces of a function $Ω$.